Cardiovascular, mortality, and kidney outcomes with GLP-1 receptor agonists in patients with type 2 diabetes: a systematic review and meta-analysis of cardiovascular outcome trials. Issue 10 (October 2019) - Kristensen, Søren L; Rørth, Rasmus; Jhund, Pardeep S; Docherty, Kieran F; Sattar, Naveed; Preiss, David; Køber, Lars; Petrie, Mark C; McMurray, John J V
Summary: Background: Glucagon-like peptide-1 (GLP-1) receptor agonists differ in their structure and duration of action and have been studied in trials of varying sizes and with different patient populations, with inconsistent effects on cardiovascular outcomes reported. We aimed to synthesise the available evidence by doing a systematic review and meta-analysis of cardiovascular outcome trials of these drugs. Methods: We searched MEDLINE (via PubMed) and the Cochrane Central Register of Controlled Trials for eligible placebo-controlled trials reporting major adverse cardiovascular events (MACE; ie, cardiovascular death, stroke, or myocardial infarction) up to June 15, 2019. We did a meta-analysis using a random-effects model to estimate overall hazard ratios (HRs) for MACE, its components, death from any cause, hospital admission for heart failure, kidney outcomes, and key safety outcomes (severe hypoglycaemia, pancreatitis, and pancreatic cancer). We also examined MACE in several subgroups based on patient characteristics (history of cardiovascular disease, BMI, age, baseline HbA1c, and baseline estimated glomerular filtration rate), trial duration, treatment dosing interval, and structural homology. Findings: Of 27 publications screened, seven trials, with a combined total of 56 004 participants, were included: ELIXA (lixisenatide), LEADER (liraglutide), SUSTAIN-6 (semaglutide), EXSCEL (exenatide), Harmony Outcomes (albiglutide), REWIND (dulaglutide), and PIONEER 6 (oral semaglutide). Overall, GLP-1 receptor agonist treatment reduced MACE by 12% (HR 0·88, 95% CI 0·82–0·94; p<0·001). There was no statistically significant heterogeneity across the subgroups examined. HRs were 0·88 (95% CI 0·81–0·96; p=0·003) for death from cardiovascular causes, 0·84 (0·76–0·93; p<0·001) for fatal or non-fatal stroke, and 0·91 (0·84–1·00; p=0·043) for fatal or non-fatal myocardial infarction. GLP-1 receptor agonist treatment reduced all-cause mortality by 12% (0·88, 0·83–0·95; p=0·001), hospital admission for heart failure by 9% (0·91, 0·83–0·99; p=0·028), and a broad composite kidney outcome (development of new-onset macroalbuminuria, decline in estimated glomerular filtration rate [or increase in creatinine], progression to end-stage kidney disease, or death attributable to kidney causes) by 17% (0·83, 0·78–0·89; p<0·001), mainly due to a reduction in urinary albumin excretion. There was no increase in risk of severe hypoglycaemia, pancreatitis, or pancreatic cancer. Interpretation: Treatment with GLP-1 receptor agonists has beneficial effects on cardiovascular, mortality, and kidney outcomes in patients with type 2 diabetes. Funding: None.